Egg Internal Quality and n-3 Fatty Acids of Native Chicken Fed on Skipjack Fish (Katsuwonus pelamis. l) Industrial Waste Containing Feed - Leke, Jein Rinny; Achmanu,; Sjofjan, Osfar; Najoan, Marie (International Journal of Poultry Science, 2013)
The objective of this study was to assess the effect of the use of skipjack fish industrial waste to native hen diets on egg internal quality. A total of 180 native laying hens 27-34 weeks of age were used in this experiment and randomly distributed into 180 units of battery cage. There were three types of skipjack waste used as main treatment diets, namely Heads and Entrails (HE) (S1), the rest of filleting (bones) (S2) and company sorting residuals (arachon) (S3). The treatment diets have five levels of skipjack waste each, hence the 15 treatment diets combination which consisted of one diet without skipjack waste (control) and the others four containing 5, 10, 15 and 20% skipjack wastes each. The experiment was carried out based on a nested completely randomized design, comprising three main treatments (A factors), five levels as sub-plot (B factors) with three replicates containing four native hens each. Data were analyzed using and the differences between treatments were tested Duncan's multiple range test. The variables measured were egg weight, Hen Day Production (HDP), egg weight, yolk color and n-3 FA. The results revealed that the main treatments HE, bones and arachon were not significantly effects (P>0.05) on HDP, egg weight and yolk color. Meanwhile, increasing the level of HE, Bones and Arachon did not affect significantly (P>0.05) against HDP, egg weight, yolk color, Furthermore, the treatments (HE, Bones, Arachon) were not significantly effects (P>0.05) on SAFA, MUFA, Σn-3, Σn-6, Ratio of n-3:n-6. Similarly, increasing the level of up to 20% of HE, Bones and Arachon to hen diets did not affect significantly (P>0.05) against SAFA, MUFA, Σn-3, Σn-6 and ratio of n-3: n-6. Therefore, the skipjack industrial waste, as Head and Entrails (HE), bones and arachon could be used to the ration for optimizing productivity of native hen. It was recommended, the level of using the skipjack waste of up to 15% in ration.